THE IMPACT OF ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF THE ECONOMIC ( ENTERPRISE – APPLE- AS A MODEL) - Zaidi, sania; Kechroud, fatma zohra (Social Empowerment Journal, 2020)
This study aims to shed light on the organizational culture in economic institutions that are the basis for the success of strategies within the institution, as each of them has a goal or a set of goals that it seeks to achieve, and some organization succeed in achieving heir goals of growth, expansion and capabilities to satisfy the needs of their customers, and Success in entering new markets and producing new products which leads to their survival and continuity, and some organizations falter and fail to achieve their goals which leads to bankruptcy and exit from the business world, And it may be that the first type and the second type are two institutions that work in the same environment and the same field and are subjected to the same environmental restrictions imposed on them, and the same assumptions available to them, and even they achieve the same type of products, but the first succeeds and the second fails, this is what The research paper will reveal it.